Enhanced optical absorption and photocatalytic activity of anatase TiO2 through CNd-codoped: A DFT+U calculations. (October 2017) - Shi, Hailong; Lin, Yanming; Jiang, Zhenyi; Su, Yunlong; Ding, Xu; Zhang, Xiaodong; Zhu, Haiyan; Zhang, Ruiqin
Abstract: The electronic and optical properties are investigated using density functional theory plus U approach in CNd monodoped and codoped anatase TiO2 . The calculated results indicate that C dopant can enhance the intensity of optical absorption and Nd dopant can extend the optical absorption range into the whole visible spectrum in CNd-codoped anatase TiO2, and the Nd 4 f states can effectively reduce the recombination of photo-excited electron-hole pairs thus achieving higher visible light photocatalytic activity for hydrogen production by water splitting than pure TiO2 . Moreover, we also study the effects of doping concentration and impurity distance in CNd-codoped anatase TiO2 system, finding that the higher doping concentration, the stronger absorption activity, and absorption activity increases with the shortness of impurity distance due to the assemblage of impurity states. Graphical abstract: Highlights: The band gap of CNd-codoped TiO2 has a remarkable decline compared with pure TiO2 . C dopant can extend the optical absorption range into the whole visible spectrum. Nd dopant can enhance the intensity of optical absorption in visible spectrum. Nd 4 f states prevent the photo-excited carriers recombination in CNd-codoped TiO2 . Our calculated results further explain the photocatalytic phenomenon in experiment.